2005
DOI: 10.5194/bg-2-125-2005
|View full text |Cite
|
Sign up to set email alerts
|

Global uptake of carbonyl sulfide (COS) by terrestrial vegetation: Estimates corrected by deposition velocities normalized to the uptake of carbon dioxide (CO<sub>2</sub>)

Abstract: Abstract. COS uptake by trees, as observed under dark/light changes and under application of the plant hormone abscisic acid, exhibited a strong correlation with the CO 2 assimilation rate and the stomatal conductance. As the uptake of COS occurred exclusively through the stomata we compared experimentally derived and re-evaluated deposition velocities (V d ; related to stomatal conductance) for COS and CO 2 . We show that V d of COS is generally significantly larger than that of CO 2 . We therefore introduced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
197
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(232 citation statements)
references
References 18 publications
19
197
4
Order By: Relevance
“…The global annual source and sink strengths are estimated to be 1.31±0.25 Tg a −1 and 1.66±0.79 Tg a −1 , respectively (Watts, 2000). However, recent investigations by Sandoval-Soto et al (2005) reveal that current estimates for the uptake of COS by vegetation seem to be underestimated and indicate that the global atmospheric budget of COS may be considered as unbalanced again.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The global annual source and sink strengths are estimated to be 1.31±0.25 Tg a −1 and 1.66±0.79 Tg a −1 , respectively (Watts, 2000). However, recent investigations by Sandoval-Soto et al (2005) reveal that current estimates for the uptake of COS by vegetation seem to be underestimated and indicate that the global atmospheric budget of COS may be considered as unbalanced again.…”
Section: Introductionmentioning
confidence: 93%
“…Besides photolysis and the reactions with OH and O in the stratosphere, vegetation and soils are regarded as the dominating terrestrial sinks (Brown and Bell, 1986;Goldan et al, 1988;Kettle et al, 2002;Sandoval-Soto et al, 2005;Chin and Davis, 1993;Kesselmeier et al, 1999). On the other hand, COS has also a chemical sink in the troposphere through reaction with OH (Chin and Davis, 1995;Kjellström, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem-scale fluxes of OCS have been proposed as a means to directly determine the photosynthetic uptake of carbon in the biosphere, independently of soil and plant respiration (1,13,14,19). However, for this approach to work as proposed, a number of requirements must be met, many of which are not realized year-round at Harvard Forest.…”
Section: Internal Leaf Conductances In Series (Following Equation 3 Imentioning
confidence: 99%
“…Leaf-scale studies have confirmed the OCS link to photosynthesis (14,15). Initial OCS ecosystem flux estimations were made using flask sampling followed by analysis via gas chromatography-mass spectrometry (GC-MS) (13,16), but these studies did not have sufficient resolution to examine daily or hourly controls on the OCS flux.…”
mentioning
confidence: 99%
“…differ [Campbell et al, 2008;Sandoval-Soto et al, 2005;Suntharalingam et al, 2008], and therefore, large uncertainties in the OCS budget remain [Kettle et al, 2002;Montzka et al, 2007] [Griffith et al, 1998;Kohlhepp et al, 2012;Paton-Walsh et al, 2004]. To ensure that differences in OCS behavior across the three sites are unaffected by the configuration of the retrieval, the same retrieval settings were used at all three sites, i.e., fitting four microwindows covering the p19 (2053.98-2054.24 [Rinsland et al, 1998]) is designed to retrieve vertical profiles of one or more gases from solar absorption FTS spectra.…”
Section: Geophysical Research Letters Research Lettermentioning
confidence: 99%